Testing and improving OMI DOMINO tropospheric NO2 using observations from the DANDELIONS and INTEX-B validation campaigns - Hains, Jennifer C.; Boersma, K. Folkert; Kroon, Mark; Dirksen, Ruud J.; Cohen, Ronald C.; Perring, Anne E.; Bucsela, Eric; Volten, Hester; Swart, Daan P. J.; Richter, Andreas; Wittrock, Folkard; Schoenhardt, Anja; et al. (Journal of geophysical research. Atmospheres, 2010)
We present a sensitivity analysis of the tropospheric NO2 retrieval from the Ozone Monitoring Instrument (OMI) using measurements from the Dutch Aerosol and Nitrogen Dioxide Experiments for Validation of OMI and SCIAMACHY (DANDELIONS) and Intercontinental Chemical Transport Experiment-B (INTEX-B) campaigns held in 2006. These unique campaigns covered a wide range of pollution conditions and provided detailed information on the vertical distribution of NO2. During the DANDELIONS campaign, tropospheric NO2 profiles were measured with a lidar in a highly polluted region of the Netherlands. During the INTEX-B campaign, NO2 profiles were measured using laser-induced fluorescence onboard an aircraft in a range of meteorological and polluted conditions over the Gulf of Mexico and the east Pacific. We present a comparison of measured profiles with a priori profiles used in the OMI tropospheric NO2 retrieval algorithm. We examine how improvements in surface albedo estimates improve the OMI NO2 retrieval. From these comparisons we find that the absolute average change in tropospheric columns retrieved with measured profiles and improved surface albedos is 23% with a standard deviation of 27% and no trend in the improved being larger or smaller than the original. We show that these changes occur in case studies related to pollution in the southeastern United States and pollution outflow in the Gulf of Mexico. We also examine the effects of using improved Mexico City terrain heights on the OMI NO2 product.